2004
DOI: 10.1021/jp0373088
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of Fluorinated Alcohols:  Reaction with Cl Atoms and OH Radicals and Atmospheric Lifetimes

Abstract: Relative rate techniques were used to study the kinetics of the reactions of Cl atoms and OH radicals with a series of fluorinated alcohols, F(CF 2 ) n CH 2 OH (n ) 1-4), in 700 Torr of N 2 or air diluent at 296 ( 2 K. The length of the F(CF 2 ) n group had no discernible impact on the reactivity of the molecule. For n ) 1-4, k(Cl + F(CF 2 ) n CH 2 OH) ) (6.48 ( 0.53) × 10 -13 and k(OH + F(CF 2 ) n CH 2 OH) ) (1.02 ( 0.10) × 10 -13 cm 3 molecule -1 s -1 . Product studies of the chlorine initiated oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
125
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(142 citation statements)
references
References 30 publications
17
125
0
Order By: Relevance
“…These authors stated that the reported absorption cross sections of CF 3 CH 2 CH 2 OH were 5-10 % lower than those previously reported by Waterland et al [28] As shown in Figure 5 a, the band positions and shapes for CF 3 CH 2 CH 2 OH are in excellent agreement with the high-resolution spectrum [39] 760 0.123 RR/FTIR Sellevåg et al [6] 4-70 0.10 DF-PLP-FP/LIF Tokuhashi et al [40] CF 3 reported by Waterland et al [28] Therefore, s n is not resolution dependent between 0.004 and 1 cm À1 .…”
supporting
confidence: 74%
“…These authors stated that the reported absorption cross sections of CF 3 CH 2 CH 2 OH were 5-10 % lower than those previously reported by Waterland et al [28] As shown in Figure 5 a, the band positions and shapes for CF 3 CH 2 CH 2 OH are in excellent agreement with the high-resolution spectrum [39] 760 0.123 RR/FTIR Sellevåg et al [6] 4-70 0.10 DF-PLP-FP/LIF Tokuhashi et al [40] CF 3 reported by Waterland et al [28] Therefore, s n is not resolution dependent between 0.004 and 1 cm À1 .…”
supporting
confidence: 74%
“…Alcohols are affected by halogen atoms either by hydrogen abstraction in α-position (Wu et al, 2003) or by oxidation to aldehydes (Hurley et al, 2004).…”
Section: Related Mechanisms Of Halogen Chemistrymentioning
confidence: 99%
“…[4][5][6] CF 3 CH 2 CH 2 OH is the one among the family of CF 3 (CH 2 ) x CH 2 OH, and its major atmospheric photooxidation product is CF 3 CH 2 CHO. [7][8][9][10] The major degradation process of CF 3 CH 2 CHO in atmosphere is initiated by the OH radicals. Experimental studies have been performed by some groups to determine the absolute and relative rate constants of the CF 3 CH 2 CHO + OH reaction.…”
Section: Introductionmentioning
confidence: 99%